Validation of the FullPIERS scale as a prognostic tool for severe preeclampsia in a high-altitude setting - Gallegos-Diaz, Carlos Antonio (2026)
Introduction: High-altitude environments predispose individuals to hypertensive disorders during pregnancy; however, the lack of laboratory facilities often limits accurate diagnosis. Objective: To determine the validity of the FullPIERS scale as a prognostic tool for severe preeclampsia in populations living at high altitudes. Materials and Methods: A cross-sectional diagnostic validation study was conducted. Medical records from 284 pregnant women with preeclampsia treated at a high-altitude hospital were reviewed. The gold standard was a clinical diagnosis, and the FullPIERS scale aimed to estimate severity based on gestational age, chest pain, platelet count, creatinine levels, aspartate aminotransferase concentrations, and oxygen saturation, using a 30% risk threshold from the FullPIERS calculator. Results: In the high-altitude hospital, 60% of pregnant women with preeclampsia developed severe disease. At a 30% threshold, the FullPIERS scale demonstrated a sensitivity of 29.21% (95% CI: 23.03–36.28%), specificity of 86.79% (95% CI: 79.04–91.97%), positive predictive value of 78.79% (95% CI: 67.49–86.92%), negative predictive value of 42.20% (95% CI: 35.84–48.84%), and accuracy of 50.70% (95% CI: 44.92–56.47%). The area under the curve was 58%. Conclusion: Using a 30% threshold, the FullPIERS scale demonstrated moderate accuracy in estimating the severity of preeclampsia in a high-altitude hospital setting.